2010
DOI: 10.1007/s11200-010-0009-7
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of soils pollution extent in surroundings of ironworks based on magnetic analysis

Abstract: This paper reports on magnetic and magnetomineralogical studies of soils influenced by ironworks activity. Researches were conducted in five areas, of which Ostrowiec wi¡tokrzyski ironworks area is described in detail. A map of magnetic susceptibility was created based on field measurements and samples taken from soil profile were analyzed in laboratory. Measurements of magnetic susceptibility in two frequency ranges, anhysteretic remanent magnetization, isothermal remanent magnetization thermomagnetic and geo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…Furthermore, the vertical distribution of magnetic susceptibility did not show a typical subsurface maximum, observed in industrially dominated soils (e.g., Spiteri et al, 2005;Fialová et al, 2006;Rosowiecka and Nawrocki, 2010). The volume magnetic susceptibility of the same samples was measured in the 3 different devices.…”
Section: Discussionmentioning
confidence: 95%
“…Furthermore, the vertical distribution of magnetic susceptibility did not show a typical subsurface maximum, observed in industrially dominated soils (e.g., Spiteri et al, 2005;Fialová et al, 2006;Rosowiecka and Nawrocki, 2010). The volume magnetic susceptibility of the same samples was measured in the 3 different devices.…”
Section: Discussionmentioning
confidence: 95%
“…Maghemite and iron sulfides were also identified. Subsequent studies have revealed a significant increase in the magnetic susceptibility of soil closest to the steel plant in the last four years (Rosowiecka & Nawrocki, 2010). Land near the steel plant is composed of fertile soil (chernozem, brown soils, loess) and is under cultivation.…”
Section: The Role Of Magnetic Susceptibility In Assessing Topsoil Conmentioning
confidence: 99%
“…Magnetic methods should be considered as a first choice and an appropriate strategy when conducting surveys [8] and they can be a helpful indicator when targeting and selecting sampling sites for subsequent geochemical analyses. These methods allow us to target the area most affected by pollution near roads and highways or industrial units, such as steel smelters [14][15][16][17], power plants [18][19][20] and cement plants [21]. These are the preferred areas for sampling in order to investigate the level of contamination by toxic elements like heavy metals, with consequent benefits in saving time, manpower and materials.…”
Section: Introductionmentioning
confidence: 99%